Nightmare on Main Street : angels, sadomasochism, and the culture of Gothic. - Edmundson, Mark, 1952- (Harvard University Press, 1999)
In an assessment of American culture on the eve of the millennium, Mark Edmundson asks why Americans are determined to be haunted, courting the Gothic at every turn, and at the same time, committed to any scheme for ready-made transcendence.